Roots that refresh : historical-theological engagement with Jewish meal traditions and the celebration of the Eucharist in the Anglican Church - Houston, Peter, C. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MTh (Systematic Theology and Ecclesiology. Church History and Church Polity))--University of Stellenbosch, 2007.